Internet search data showed increased interest in supplementary online education during the COVID-19 pandemic, with females showing a greater increase - Wang, Pengyuan; Jiang, Li; Yang, Jian (Frontiers in Education, 2023)
The COVID-19 pandemic has led to tremendous disruptions in people’s everyday activities, including the pursuit of education. Internet search data may provide insights into potential audiences’ interest in online education. Using Internet search data, we examined the impact of COVID-19 on people’s interest in supplementary online education in the US over nine months (10/14/2019-07/19/2020). We found there was increased interest in supplementary online education after WHO announced COVID-19 as a pandemic, with a greater increase among females than males. We found that the increased interest in online education persisted after the stay-at-home orders were lifted; in addition, we identified concerns over unemployment as a key variable that significantly explained the variance in the interest in online education, even after controlling for COVID cases and deaths. Policymakers and online education platforms may take advantage of people’s, especially women’s increased interest in online education when designing policies or marketing mix.